A brincadeira da cultura tradicional da infância na formação musical do pedagogo - Traverzim, Monique [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research aims to show that it is possible to Educator, without specific training in Music, take responsibility for Music Education classes in Basic Education, specifically in kindergarten and elementary school. It is a qualitative research and the data collection was made using: a) questionnaires, b) experience reports, and c) a participant observation of a Research Seminar, which was prepared by the researcher, based on Play of Traditional Culture of Childhood. According to General Systems Theory and Culture of Childhood, our premise was that the human being is a 'playing' being; what was ratified when observing that, when the teacher is playing, there is no prejudice about self-production in music making, and also that these teachers feel able to conduct a musicalization class with their students. From the class teachers results concerning to the: 1) participation, 2) involvement, 3) dedication during the course of the seminar, and 4) the actions they have developed in schools where they operate; we inferred that they can carry on what the new Brazilian legislation demands about teaching Music with Children's Play. We hope that, with this research, it is possible to contribute to the Pedagogy professionals, specially, if it: 1) increases their confidence in approaching to the music, 2) assists them in Music teacher training, and 3) collaborates with elements for further work on the subject

A presente pesquisa buscou mostrar que é possível ao Pedagogo, sem formação específica em Música, responsabilizar-se pelas aulas de Educação Musical na Educação Básica, especificamente na Educação Infantil e nos Anos Iniciais do Ensino Fundamental. A pesquisa foi qualitativa e a coleta de dados feita por meio de: a) aplicação de questionários, b) coleta de relatos de experiência e c) observação participante de um Seminário de Pesquisa baseado nas Brincadeiras da Cultura Tradicional da Infância, elaborado pela Pesquisadora. Considerando a premissa de que o homem é um ser brincante e amparando-se na Teoria Geral dos Sistemas e na Cultura da Infância, foi possível observar que, por meio do Jogo, o professor não tem preconceito com o fazer musical e sente-se capaz de conduzir um trabalho de musicalização com seus alunos. A partir da participação, envolvimento e dedicação dos professores de classe durante a realização do Seminário, e as ações por eles desenvolvidas nas escolas, nas quais atuam, infere-se que eles podem dar conta do que a nova legislação brasileira pede em relação ao Ensino de Música tendo como base as Brincadeiras Infantis. Espera-se, com esta Pesquisa, contribuir com os profissionais da área da Pedagogia, em especial se puder aumentar-lhes a confiança na aproximação com a Música, auxiliar na formação musical de professores e colaborar com elementos para novos trabalhos acerca do tema
Keywords: Professores - Formação; Jogos musicados; Educação de crianças; Musica - Instrução e estudo; Music Instruction and study